Between Bath and Bosnia: Jane Austen and Croatian Culture - Jukić, Tatjana (Array, 2007)
The text analyzes how reading and translating Jane Austen in Croatia forms as a symptom of the specific makeup of local cultural history (informing its take on social realism and post-socialism).